The existential crisis of traditional shopping streets: the sun model and the place attraction paradigm - Carmona, Matthew (Journal of urban design, 2022)
This paper explores the crisis in our traditional shopping streets driven by the rapid move to shopping online. The paper examines the nature of traditional shopping streets; why physical and local shopping is important; conceptualizes the distinguishing characteristics of traditional forms of retail and online shopping alongside the factors that determine shopping choices; and explores different approaches to shaping the future of traditional shopping streets. Ultimately, it asks, what are the key place-based intervention factors that can help to guarantee a future for traditional shopping streets?